Arteritis Takayasu - Wira Pratama Yasa, Anak Agung Gede; Lina Kamelia, Luh Putu; Lestari, Made Widya (PERDOSNI, 2022)
Takayasu Arteritis is a rare autoimmune rheumatic disease that causes chronic granulomatous vasculitis of the large arteries such as the aorta and its branches. The disease is often associated with stroke at young age. The mortality and morbidity rates in young age patients are quite significant. The ability to recognize the disease are based on etiopathology, clinical classification, and diagnostic support. Those are crucial to establish a proper treatment and maintain an adequate prognosis. Takayasu's arteritis remains a challenge because diagnosis is often delayed and there is currently no sensitive and specific gold standard for monitoring inflammatory disease.